Kajian etnobotani pemanfaatan jenis-jenis pohon oleh masyarakat etnik kuri di kabupaten Teluk Wondama - Simson Samberi; Soetjipto Moeljono; Jonni Marwa (Cassowary, 2019)
The Kuri ethnic group is one of the largest tribes in the Teluk Wondama Regency which is now a group minority even though in the past they had vast forests and well-organized levels of civilization. The local knowledge of the Kuri ethnic group which is passed on to the next generation does not hold well. This can be proven by the fact that there are many people who no longer use forest functions in their entirety. Utilization of Trees by the Kuri Ethnic Community in Teluk Wondama Regency was carried out in 3 villages of Wombu, Werianggi and Dusner. Wombu Village Naekere District has 75 types, Werianggi Village Nikiwar District has 62 types, Dusner Village Kuri Wamesa District has 45 types. There are 9 (nine) forms of utilization of trees by the Kuri ethnic community in the villages of Wombu, Werianggi and Dusner, namely: building materials / houses, home furnishings, food, medicine, magic, crafts and arts, economy, customs and hunting / transportation tools. The average use of most forms for the needs of tools / hunting 25.33 species of trees. The most used trees are; Matoa trees (pometia sp), Genemo (Gnetum gnemon), langsat (lansium domestucum) and Albisia (paraseriantes falcataria). Species similarity was determined using the Jaccard community similarity index, the results showed there were differences in tree species in the three villages, Wombu-Dusner 16.4%, Wombu-Werianggi 8.62%, Dusner-Werianggi 58.51%. The part of the tree that is utilized is the root, trunk, bark, sap, fruit and leaves. The part that is mostly utilized by the Kuri Ethnic in three locations is the trunk of 49 species of trees for Wombu village, 36 species in Werianggi village and 35 species in Dusner village. Community knowledge is grouped into two young generations (15-25) years and older generations (60 years and older) and research locations. The research data is cascaded with a tiered scale starting from ever heard of, never seen and never used. The results of the study show that never heard of 36.35 and have seen 40.83 in the moderate category, never used 29.36 in the small category. Knowledge difference between generations is done by U-test. The results showed that in Wombu village there were no differences in knowledge between young and old groups. In the villages of Werianggi and Dusner there are differences in knowledge between old and young age. Kuri ethnic local wisdom as a form of conservation in the form of religious values ​​and social values, the existence of binding traditional rules such as sasi and places of pamali must be maintained and is a joint responsibility of both the government, NGOs and the community so that the availability of species that have economic value for the Kuri ethnic community is always available.